2014
DOI: 10.4321/s1886-36552014000200002
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the adherence to and the therapeutic effectiveness of hypolipidemic agents in a population of patients in Brazil: a retrospective cohort study

Abstract: *Objective: to evaluate the relation between patient adherence and therapeutic effectiveness of hypolipidemic agents in clinical practice. Methods: A retrospective cohort study of 417 patients using hypolipidemic drugs (simvastatin, atorvastatin) between 2003 and 2010 was performed. The population studied consists of patients assisted by the Public Health Service in the far-west region of the State of Santa Catarina, Brazil. The Medication Possession Ratio obtained from pharmacy refill data was used to measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Parallel to findings from a previous study, adherence to medication was reported to reduce significantly over time. 29 In the study by Cunico et al good adherence to antihyperlipidemia was observed in 90% of patients in the first 8 months of treatment, but it reduced to approximately 80% after 20 months. 29 These results show that over time, it is imperative that the importance of medication adherence be emphasized for patients with long-term medication use.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Parallel to findings from a previous study, adherence to medication was reported to reduce significantly over time. 29 In the study by Cunico et al good adherence to antihyperlipidemia was observed in 90% of patients in the first 8 months of treatment, but it reduced to approximately 80% after 20 months. 29 These results show that over time, it is imperative that the importance of medication adherence be emphasized for patients with long-term medication use.…”
Section: Discussionmentioning
confidence: 95%
“… 29 In the study by Cunico et al good adherence to antihyperlipidemia was observed in 90% of patients in the first 8 months of treatment, but it reduced to approximately 80% after 20 months. 29 These results show that over time, it is imperative that the importance of medication adherence be emphasized for patients with long-term medication use. The current study also found that patients with human immunodeficiency virus were nine times more likely to be adherent to medication than patients with chronic kidney disease (OR 9.08, 95% CI 3.25–25.3, P <0.05).…”
Section: Discussionmentioning
confidence: 95%
“…It reduces the patients’ quality of life, wastes health care resources, and increases health care costs. [ 8 9 10 ]…”
Section: Introductionmentioning
confidence: 99%
“…In addition, atorvastatin has been identified as the most cost-effective option for patients with dyslipidemia in the Colombian health context when moderate to high intensity treatments are required 14 . When comparing these results with studies from other countries, atorvastatin has also been the most prescribed in Taiwan, but only at 37% 15 , whereas research in Italy and Brazil found a predominance of simvastatin 16 , 17 .…”
Section: Discussionmentioning
confidence: 68%